Association of Midkine and Pleiotrophin Gene Polymorphisms With Systemic Lupus Erythematosus Susceptibility in Chinese Han Population - Wang, Peng; Mao, Yan-Mei; Zhao, Chan-Na; Wang, Jie-Bing; Li, Xiao-Mei; Ye, Dong-Qing; Pan, Hai-Feng (Frontiers in Immunology, 2020)
In previous study, we have reported an increased plasma midkine (MK) and pleiotrophin (PTN) concentrations in patients with systemic lupus erythematosus (SLE), and the increase of MK and PTN associated with inflammatory cytokines IL-17 level and some clinical manifestations, suggesting the underlying association of MK and PTN with SLE. This study was conducted to investigate the association between common single-nucleotide polymorphisms (SNPs) in the MK and PTN gene and SLE susceptibility. A total of 989 subjects (496 SLE patients and 493 healthy controls) were included and genotyped for three MK SNPs and seven PTN SNPs in using improved multiple ligase detection reaction (iMLDR). Results have demonstrated no significant differences for genotype and allele frequencies in all 10 SNPs between SLE patients and healthy controls. Case-only analysis in SLE revealed that, in MK gene, the genotype frequency of AA/AG (rs35324223) was significantly lower in patients with photosensitivity than those without; the allele frequency of A/G (rs20542) was significantly higher in patients without serositis. In PTN gene, the A/G allele frequency (rs322236), C/T allele frequency and TT/CT genotype frequency (rs6970141) appeared significantly increased results in patients with immunological disorder compared to those without. Furthermore, no significant differences in plasma MK and PTN concentrations with its SNPs genotypes were found. MK and PTN SNPs showed no associations with SLE genetic susceptibility, but it may be associated with the course of this disease; further studies are needed to focus on the mechanism of MK and PTN genes in the pathogenesis of SLE.